L’editore Salvatore De Carlo e il mondo slavo - Leto, Maria Rita (Status Quaestionis, 2022)
The essay aims at retracing the trajectory of Salvatore De Carlo (1913-1988), publisher of various anthologies and foreign books in translation between the end of World War II and the post-war period in Italy. Despite the sheer volume and variety of his publications, this figure is virtually ignored both by critics and historians. The article specifically focuses on De Carlo’s contribution to the diffusion of knowledge of Slavic literatures, especially Russian, in our country. To this end, the publisher enrolled as editors the most prominent Slavic scholars of those years, Ettore Lo Gatto and Enrico Damiani. Curiously, however, the volumes edited by the founders of the discipline in our country are all but neglected even by bibliographic repertoires. In reconstructing the editorial history of these anthologies, the article also suggests a possible explanation for the silence that has so far surrounded this publisher.